Harmonisasi Antara Kepolisian, Kejaksaan Dan Komisi Pemberantasan Tindak Pidana Korupsi (Kpk) Dalam Penyidikan Tindak Pidana Korupsi Di X - Ghazal Khairullah; Gibran Hanif (Universitas Sains dan Teknologi Komputer, 2023)
The definition of Creative Economy (Ekraf) according to Law Number 24 of 2019 concerning Creative Economy is the embodiment of added value from intellectual property originating from human creativity based on cultural heritage, science and/or technology. The meaning of creativity contained in the definition of the creative economy can be seen as the capacity or effort to produce or create something unique, create a solution to a problem or do something different from the norm (thinking outside the box). The definition of the Creative Economy is then further emphasized through Presidential Regulation Number 142 of 2018 which states that ideas or ideas for intellectual property are original works, born from human intellectual creativity, based on science and technology, skills, and cultural heritage.